Draft genome sequence of Escherichia coli ST977: A clinical multidrug-resistant strain harbouring blaNDM-3 isolated from a bloodstream infection. (June 2018) - Li, Xi; Sun, Long; Zhu, Yongze; Shen, Mengyuan; Tu, Yuexing
Abstract: Objectives: The emergence of carbapenem-resistant Escherichia coli has become a serious challenge to manage in the clinic because of multidrug resistance. Here we report the draft genome sequence of NDM-3-producing E. coli strain NT1 isolated from a bloodstream infection in China. Methods: Whole genomic DNA of E. coli strain NT1 was extracted and was sequenced using an Illumina HiSeq™ X Ten platform. The generated sequence reads were assembled using CLC Genomics Workbench. The draft genome was annotated using Rapid Annotation using Subsystem Technology (RAST). Bioinformatics analysis was further performed. Results: The genome size was calculated at 5, 353 620 bp, with 5297 protein-coding sequences and the presence of genes conferring resistance to aminoglycosides, β-lactams, quinolones, macrolides, phenicols, sulphonamides, tetracycline and trimethoprim. In addition, genes encoding virulence factors were also identified. Conclusions: To our knowledge, this is the first report of an E. coli strain producing NDM-3 isolated from a human bloodstream infection. The genome sequence will provide valuable information to understand antibiotic resistance mechanisms and pathogenic mechanisms in this strain. Close surveillance is urgently needed to monitor the spread of NDM-3-producing isolates.